(untitled) (REMUNOM, 2025)
This article analyzes the civil liability of physicians and other healthcare professionals within the Brazilian legal system, emphasizing the distinction between subjective and objective liability in the context of medical practice. The research question is to understand how Brazilian law balances patient protection and the legal security of healthcare professionals, considering the risks inherent in medical practice. The overall objective is to examine the legal and doctrinal foundations that regulate the civil liability of these professionals and hospital institutions. Specifically, it seeks to identify the situations in which each form of liability applies and the criteria adopted by the courts. The research adopts a legal-dogmatic methodology, based on the analysis of legislation, specialized doctrine, and national jurisprudence. The relevance of the topic stems from the need to harmonize the right to compensation for damages with the preservation of physicians’ technical autonomy, in a context of increasing judicialization of medicine. It should be noted that, while physicians are generally held liable subjectively, upon proof of fault, hospitals and the State can be held objectively liable, provided that the damage and a causal link are demonstrated. The importance of expert evidence and medical records in determining fault is also emphasized, as is the reparative and preventive role of medical civil liability in promoting ethics, trust, and the effectiveness of the fundamental rights to health and life.